Kontribusi Kepemimpinan Pelayan, Iklim Kerja, Motivasi Kerja, Kepuasan Kerja Terhadap Disiplin Kerja Guru di SMA Negeri Kecamatan Kuta Utara Kabupaten Badung - T.S. Wulandari; A.A.G. Agung; I.P.W. Ariawan (Jurnal Administrasi Pendidikan Indonesia, 2022)
This study aimed to identify: (1) the contribution of servant leadership towards teachers’ work discipline, (2) the contribution of work climate towards teachers’ work discipline, (3) the contribution of work motivation towards teachers’ work discipline, (4) the contribution of job satisfaction towards teachers’ work discipline, (5) the contribution of servant leadership, work climate, work motivation, job satisfaction simultaneously towards the work discipline of teachers at public high schools in the sub-district of Kuta Utara, Badung regency. The population in this study was 85 teachers, with a total sample of 85 teachers. This study is classified as ex-post-facto with descriptive statistics analysis, simple correlation, partial correlation, multiple correlation, and multiple regression data analysis design. The data for this study were collected by using the Five-point Likert scale questionnaire model. The results show that: 1) There is a positive and significant correlation between servant leadership and work discipline with 0,332 (ryx1) product moment coefficient correlation, 0,301 (ry.x1-x2,3,4) partial correlation coefficient, and 7,60% contribution of servant leadership towards work discipline, 2) There is a positive and significant correlation between work climate and work discipline with 0,469 (ryx2) product moment coefficient correlation, 0,466 (ry.x2-x1,3,4) partial correlation coefficient, and 17,97% contribution of work climate towards work discipline, 3) There is a positive, but insignificant correlation between work motivation and work discipline with 0,256 (ryx3) product moment coefficient correlation, 0,194 (ry.x3-x1,2,4) partial correlation coefficient, and 3,70% contribution of work motivation towards work discipline, 4) There is a positive and significant correlation between job satisfaction and work discipline with 0,502 (ryx4) product moment coefficient correlation, 0,471 (ry.x4-x1,2,3) partial correlation coefficient, and 19,73%, contribution of job satisfaction towards work discipline, and 5) There is a positive and significant correlation of servant leadership, work climate, work motivation, job satisfaction and work discipline with Ry.1234 multiple correlation coefficient of 0,700 and there is a contribution of servant leadership, work climate, work motivation, job satisfaction and work discipline simultaneously by 49,00%.